Monitoring of the dissemination of Salmonella in the chicken Frankfurt-sausage production line of a sausage factory in the state of São Paulo, Brazil - de Freitas Luiz, A.; Moreira, F. C.; Correa, E. D.; Falcao, D. P. (Fundacão Oswaldo Cruz, 2004)
Poultry meat and its derivatives are among the foodstuffs considered by environmental health authorities to present the highest risks to the public. A total of 185 samples were collected in five monthly batches, from different processing stages in a sausage plant that uses mechanically-deboned chicken meat (MDCM) and tested for the presence of Salmonella. Enrichment was carried out in both Kauffman tetrathionate broth and Rappaport-Vassiliadis broth and isolation on Salmonella-Shigella agar and brilliant-green agar. Live Salmonella bacteria were isolated from six samples of the raw meat and from the emulsion, in batches three, four and five, but not from any sample in batches one or two. The six isolated strains were all classified as Salmonella Albany, which has not previously been reported in MDCM. of the two enrichment broths, Rappaport-Vassiliadis gave the better results. The Pattern of contamination suggests a probable common source, given that a new supplier was used in the third, fourth, and fifth months. It was also shown that the industrial cooking was effective in preventing Salmonella surviving in the final product.
Keywords: Salmonella; chicken Frankfurt-sausage; mechanically-deboned chicken meat (MDCM); industrial monitoring